Creating an Enjoyable Learning Experience in Problem-Based Learning to Enhance Creative Thinking of Junior High School Students - Diva Larasati; Yayuk Mulyati; Erti Hamimi (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Creative thinking skills (CTS) of students in Indonesia are still low, as shown by various international assessments. Although the problem based learning (PBL) learning model has been proven effective in improving students' creativity, there are still limitations in its application, especially when students lack confidence or interest in solving problems. Therefore, this study aims to compare the effectiveness of the enjoyable learning in problem based learning (EL-PBL) learning model with PBL learning in improving students' CTS on excretory system material. The research method used was quantitative method with quasi-experiment design, namely non-equivalent control group design. The experimental class applied EL-PBL, while the control class used PBL. The pretest-posttest questions were valid (r> 0.361) and reliable (pretest 0.765; posttest 0.801). The t-test results showed that there was a significant difference from learning in the experimental and control classes as shown in the results of sig. 0.009 (p < 0.05), with N-Gain results of 0.50 (medium category) in EL-PBL class and 0.35 (medium category) in PBL class. The four CTS indicators show more trained in EL-PBL classes than PBL classes. Thus, EL-PBL can be an alternative in junior high school students' CTS efforts through a more interactive and fun learning experience